Bioaccumulation as a mechanism of microbiome/drug interactions. Issue 2 (February 2022) - Cohen, Ziv; Kelly, Libusha
Abstract : Microbes of the human gut can change drug disposition in the human body and gut ecology via 'bioaccumulation', a process in which bacteria take up compounds intracellularly without chemically modifying them or experiencing changes in growth, as described in Klünemann et al . This work expands current understanding of the types of drug–bacterial interactions in the gut environment.